Waterborne polyurethane / acrylate hybrid resin, fast-drying waterborne automotive coatings and their preparation methods
Patent Information
- Application Number
- CN202611392492.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-11-20
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-20
AI Technical Summary
目前主要的催干剂大多数为含有钴、锰、铅等金属元素的化合物,一方面金属离子在体系中可能会影响其他涂层性能,尤其是对金属离子比较敏感的电泳漆层;另一方面很多金属离子自带颜色,对于色漆层也会有一定影响
1)本发明提供了一种水性聚氨酯/丙烯酸酯杂化树脂分散液,通过采用磺酸铵盐扩链剂,在确保分散液稳定性和低粘度的条件下,有效提升了分散液的固含量,高于本申请对比例所采用的市售水性聚氨酯/丙烯酸酯分散液固含量,达到不低于52.5%,甚至可以达到62.5%固含;
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer materials, and specifically relates to a high-solids-content, low-viscosity polyurethane / acrylate hybrid resin, a fast-drying waterborne automotive coating, and a method for preparing the same.
[0002] This invention claims priority. The earlier application, application number 202511711015.3, entitled "Waterborne polyurethane / acrylate hybrid resin, fast-drying waterborne coating for automobiles and preparation method thereof," was filed on November 20, 2025. Background Technology
[0003] As one of the major VOC-emitting industries, the shift from oil-based to water-based coatings is urgent. However, water-based coatings still face many technical challenges that need to be overcome. Besides functional hurdles, application performance is also a major factor hindering the transition. "Oil-to-water" coatings use water as a solvent to replace highly volatile organic solvents. Therefore, slow drying speed is a major problem during application. This is especially true for automotive water-based coatings, where water vapor accumulates on the coating surface during application, hindering subsequent evaporation and significantly reducing production efficiency. Furthermore, due to multi-layer coatings, in wet-on-wet processes, incomplete drying of the underlayer can lead to poor interlayer miscibility, poor adhesion, reduced functionality of functional layers, and color bleeding / bleeding.
[0004] Therefore, solving the problem of rapid drying of water-based coatings for automobiles is an important technology for promoting the "oil-to-water" conversion. Currently, the main solutions to the rapid drying problem of water-based coatings include: 1) CN115651520A discloses the use of a drying agent to improve the drying rate of water-based automotive coatings; 2) CN114702885A discloses the use of ammonia as a neutralizing agent, adding excess ammonia during resin preparation, and then evaporating the excess ammonia during use to lower the pH value of the system and catalyze cross-linking and curing. Most of the current drying agents are compounds containing metal elements such as cobalt, manganese, and lead. On the one hand, metal ions in the system may affect the performance of other coatings, especially electrophoretic paint layers which are sensitive to metal ions; on the other hand, many metal ions have inherent color, which can also affect color paint layers. Furthermore, ammonia itself has a strong pungent odor and is harmful to human health and the environment. Directly using excess ammonia evaporation to achieve rapid drying will lead to an increase in ammonia concentration in the work area, affecting the construction environment.
[0005] Aqueous emulsions are two-phase systems. Initially, the viscosity of the system doesn't change much as water evaporates. However, when the volume of the emulsion particles reaches a critical value relative to the total system volume, the system suddenly changes from liquid to solid – a discontinuous process. Generally, the higher the solid content of the emulsion, the closer it is to the surface drying threshold, and the faster the drying speed. Increasing the solid content of the emulsion through the synthesis process can effectively shorten the drying rate of the product, which is a direct and effective measure to solve the problem of fast drying in water-based automotive coatings. Summary of the Invention
[0006] Waterborne automotive coatings not only need to provide aesthetic effects such as a smooth appearance and vibrant colors, but also need to possess various resistances, including resistance to acids, alkalis, salt spray, damp heat, and weathering. Simultaneously, they must meet the ever-increasing demands for application performance, achieving rapid drying and improving production efficiency. The purpose of this invention is to provide a novel waterborne polyurethane / acrylate hybrid resin, a waterborne automotive coating, and a method for preparing the same, suitable for waterborne automotive coatings that balance functional and application properties.
[0007] The present invention aims to solve the above-mentioned problems and provides an aqueous polyurethane / acrylate hybrid resin comprising the following structure:
[0008] Among them, R1, R2, and R3 are independently C1~C12 alkyl groups, or cycloalkyl or phenyl groups with a maximum of two C1~C4 substituents; A and Q are independently O or NR, where R is H or C1~C4 alkyl; R0 is a C2~C7 trivalent alkyl group, and A and Q are not on the same carbon atom; pol The main chain is a polyurethane / acrylate hybrid resin; and by weight, the total mass of the ammonium sulfonate structure accounts for 2.55~3.75% of the total mass of the polyurethane / acrylate hybrid resin; the ratio of the total mass of the polyurethane component to the total mass of the polyacrylate component is (0.9~1.5):1.
[0009] The present invention also provides a method for preparing the above-mentioned aqueous polyurethane / acrylate hybrid resin dispersion, comprising at least the following steps: Step S1: Add polyol to the reactor and remove water using a vacuum pump at 110-130℃ until no more bubbles appear in the polyol; cool to 78-82℃, add isocyanate, react for 15 min, add catalyst, and continue reacting for 3 h; cool to 58-62℃, then add chain extender and acetone, and continue reacting for 4 h; cool to 38-42℃, stir continuously, add deionized water within 5 min, then immediately add neutralizer to neutralize, reaching pH 7.5-9.0; add ethylenediamine as a chain extender and extend the chain for 15 min, then remove acetone and keep warm for 4 h to obtain polyurethane dispersion prepolymer; Step S2: Weigh acrylic acid and / or acrylate monomers and / or methacrylic acid and / or methacrylate monomers and / or styrene monomers and mix them evenly to obtain a monomer mixture for later use; weigh the initiator and dissolve it in a solvent to obtain an initiator solution for later use; introduce nitrogen gas into the polyurethane dispersion prepolymer obtained in Step S1 above, and heat it to 80~85℃ under a nitrogen atmosphere; after stabilizing for 5 min, add the pre-prepared monomer mixture and initiator solution dropwise, with the monomer mixture added within 180 min and the initiator solution added within 200 min; continue stirring and reacting for 1 h, add a pH adjuster, and the pH reaches 7.5~9.0 to obtain an aqueous polyurethane / acrylate hybrid resin dispersion.
[0010] The above reactions include the synthesis reaction of polyurethane prepolymer, chain extension reaction, and emulsion copolymerization reaction of acrylate monomers. The proportions of polyols, isocyanates, etc. can be determined according to the proportions of each block in the structural formula, which will not be elaborated in detail in this invention.
[0011] The dispersion contains a solid content of not less than 52.5 wt%, and the solid component is a polyurethane / acrylate hybrid resin. At 25°C, the viscosity measured by a Tu-4 cup viscometer is not higher than 25 s or measured by a rotational viscometer is not higher than 600 mPaS, and the conductivity of the deionized water used is not higher than 10 μS / cm.
[0012] Furthermore, the chain extender used contains the following structure (2):
[0013] Among them, R1, R2, and R3 are independently C1~C12 alkyl groups, or cycloalkyl groups or phenyl groups with C1~C4 atoms; A and Q are independently O or NR, where R is H or C1~C4 alkyl group; R0 is a C2~C7 trivalent alkyl group, and A and Q are not on the same carbon atom.
[0014] As a preferred embodiment of the above scheme, various raw materials were used in the preparation of the above-mentioned aqueous polyurethane / acrylate hybrid resin dispersion, mainly including: The polyol used may be one or more of polyester diol, polycarbonate diol, polyether diol, or hybrid diol, and the molecular weight of the polyol is between 1000 and 4000 Da, preferably between 2000 and 3000 Da; more preferably, the polyol used is a blend of polyester diol and polyether diol, and the ratio of polyester polyol to polyether polyol by weight is 1:(0.15 to 0.55); even more preferably, the polyol used is a hybrid diol, and the ratio of polyester and / or polycarbonate to polyether segments by weight is 1:(0.15 to 0.55). Meanwhile, the isocyanate used may be selected from one or more of isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), dicyclohexylmethane diisocyanate (HMDI), diphenylmethane diisocyanate (MDI), hydrogenated phenyl diisocyanate (H6XDI), phenyl diisocyanate (XDI), lysine diisocyanate (LDI), hydrogenated terephthalic diisocyanate (CHDI), and their oligomeric polyisocyanates. Preferably, the isocyanate used may be one or more of IPDI, HDI, HMDI, H6XDI, CHDI, and their oligomeric polyisocyanates; more preferably, the isocyanate used may be one or more of IPDI, HMDI, CHDI, and their oligomeric polyisocyanates. Meanwhile, the catalyst used can be selected from tertiary amine catalysts, morpholine catalysts, pyridine catalysts, piperazine catalysts, imidazole catalysts, and organometallic catalysts. Preferably, the catalyst used can be a tertiary amine catalyst or an organometallic catalyst. More preferably, the catalyst used is an organometallic catalyst. Even more preferably, the catalyst used is an organobismuth catalyst. Meanwhile, the neutralizing agent used may be ammonia, triethylamine (TEA) and / or dimethylethanolamine (DMEA), with TEA and / or DMEA being preferred; The acrylate monomers used in this invention can be one or more of the acrylate monomers containing structural modifications of (3), (4), (5), and (6); the methacrylate monomers used in this invention can be one of the methacrylate monomers containing structural modifications of (3), (4), (5), and (6), for example, 1-(2-hydroxyethyl)-2,2,6,6-tetramethylpiperidine methacrylate, 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole; Furthermore, by weight, the total mass of monomers containing structural modifications of (3), (4), (5), and (6) accounts for no less than 2.5% of the total mass of the monomer mixture.
[0015]
[0016] Among them, R4, R6, R7, R8 and R10 are independently H, C1-C12 alkyl, C1-C12 hydroxy-substituted alkyl, C1-C8 carbonyl; and R4, R6 and R7 contain only one acrylate group or methacrylate group; R8 and R10 contain only one acrylate group or methacrylate group. R5 and R9 are independently C1-C6 alkylene groups or none; R11 is a C1-C6 alkylene or C1-C6 alkeneoxy group and is linked to an acrylate monomer.
[0017] R12, R13, R14, R15, R16, R17, R18, R19, and R20 are independently H, C1-C12 alkyl, C1-C12 hydroxy-substituted alkyl, or C1-C12 alkoxy; and one of R12, R13, R14, R15, R16, R17, R18, R19, and R20 contains an acrylate group or a methacrylate group; and at least one of R16 and R20 is a phenolic hydroxyl group.
[0018] The acrylate monomers used in this invention include one or more of the following: methyl acrylate, ethyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, isooctyl acrylate, n-octyl acrylate, lauryl acrylate, hydroxyethyl acrylate, isobornyl acrylate, hydroxypropyl acrylate, and glycidyl acrylate; the methacrylate monomers used include one or more of the following: methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, isooctyl methacrylate, n-octyl methacrylate, lauryl methacrylate, hydroxyethyl methacrylate, isobornyl methacrylate, hydroxypropyl methacrylate, and glycidyl methacrylate. Simultaneously, at least one of hydroxyethyl acrylate (HEA) and hydroxyethyl methacrylate (HEMA) is contained, and the total weight of hydroxyethyl acrylate and hydroxyethyl methacrylate accounts for 15% to 35% of the total mass of the monomer mixture by weight; that is...
[0019] in, m HEMA , m HEA and m monomer The values represent the weights of HEMA, HEA, and each monomer, respectively. When the proportions of HEMA and HEA are less than 15%, the dispersibility of the resulting resin in water-based solvents decreases, and when applied to water-based automotive coatings, the stability of the product is significantly reduced. When the proportions of HEMA and HEA are greater than 35%, the resulting resin has excessive water absorption, and when applied to water-based automotive coatings, the workability (fast-drying properties) of the product begins to decrease, while the water resistance of the resulting coating also begins to decline.
[0020] Simultaneously, at least one of acrylic acid (AA) and methacrylic acid (MAA) is present, and the total weight of acrylic acid and methacrylic acid accounts for 2.5% to 7.5% of the total mass of the monomer mixture by weight; that is...
[0021] in, m AA , mMAA and m monomer These represent the weights of AA, MAA, and each monomer, respectively. When the proportions of AA and MAA are less than 2.5%, the adhesion of the resulting resin to the substrate will decrease significantly, reducing the adhesion strength of the final product. When the proportions of AA and MAA are higher than 7.5%, the water absorption of the resulting resin will become too high, reducing the workability of the product. At the same time, it will lead to a significant increase in the amount of pH adjuster used, which will reduce the stability of the final product.
[0022] More preferably, the total weight of HEA and HEMA accounts for 20% to 35% of the total mass of the monomer mixture, and the total weight of AA and MAA accounts for 3% to 5.5% of the total mass of the monomer mixture, thereby optimizing the overall performance of the polyurethane / acrylate hybrid resin dispersion.
[0023] The initiators used include one or more of organic peroxide initiators, inorganic initiators, and azo initiators; inorganic initiators are preferred; inorganic persulfate initiators are more preferred.
[0024] Those skilled in the art should know that if the initiator solution is dissolved in an organic solvent, the solvent needs to be removed under reduced pressure, followed by incubation for 8 hours; if the initiator solution is dissolved in deionized water, it can be directly incubated for 8 hours to obtain an aqueous polyurethane / acrylate hybrid resin dispersion for later use.
[0025] The present invention also provides a fast-drying waterborne automotive coating comprising the aforementioned waterborne polyurethane / acrylate hybrid resin, wherein the contents of each component by weight are as follows: Component A: 28-40 parts by weight of waterborne polyurethane / acrylate hybrid resin dispersion; Component B: 0.2~1.0 parts by weight of defoamer; Component C: 0.5~7.5 parts by weight of film-forming aid; Component D: 12-22 parts by weight of inorganic filler; Component E: 0.6~1.2 parts by weight of dispersant; Component F: 7.5~17.5 parts by weight of water-based pigment; Component G: 0.5~5 parts by weight of curing agent; Component H: 0.3-5 parts by weight of other additives; The solid component of the aqueous polyurethane / acrylate hybrid resin dispersion is the polyurethane / acrylate hybrid resin as described in claim 1, the solvent is deionized water, the solid content is not less than 52.5 wt%, the viscosity measured by a Tu-4 cup viscometer is not higher than 25 s or measured by a rotational viscometer is not higher than 600 mPaS, and the conductivity of the deionized water used is not higher than 10 μS / cm.
[0026] The curing agent is a carbodiimide-based curing agent. The introduced carbodiimide structure can effectively react excess carboxyl groups during the curing stage, improving the product's water resistance, damp heat resistance, and alkali resistance. Specifically, it includes the following structure (7): ; The curing agent has a molecular weight between 1200 and 6000, preferably between 1500 and 3500, and the carbodiimide structure accounts for no less than 8.5% of the total molecular chain weight. Carbodiimide curing agents containing polyethylene glycol segments are preferred.
[0027] Furthermore, the defoamer includes one or more of organosilicon defoamers, polyether defoamers, and polyether-modified polysiloxane defoamers, preferably polyether-modified polysiloxane defoamers; the film-forming aid includes one or more of alcohol-based film-forming aids, alcohol ether-based film-forming aids, alcohol ester-based film-forming aids, and other film-forming aids such as N-methylpyrrolidone; the inorganic filler includes one or more of water-based silver aluminum paste, titanium dioxide, mica powder, barium sulfate, and silica, preferably water-based silver aluminum paste; the water-based color paste includes ordinary water-based color paste, water-based color paste with matte effect, water-based color paste with metallic glitter pigment, and water-based color paste with pearl effect; the other aids include one or more of wetting agents, leveling agents, rheology modifiers, and cosolvents.
[0028] Among them, wetting agents can be selected from BYK-800, BYK-346, TEGO-500, AFCONA-3585, etc.; The leveling agent can be a polyether siloxane leveling agent or an alkali-swellable leveling agent, for example TEGO-410, TEGO-425, Disparlon AQ-600, FX-1070, etc. Among them, rheology modifiers can be polyacrylates, cellulose ethers, associative alkali swelling agents, etc., such as Borchi Gel-0620 and Hemings-299; The fourth objective of this invention is to provide a fast-drying waterborne automotive coating for use in automotive waterborne coatings. The automotive waterborne coating has fast-drying properties, which can effectively improve production efficiency, and at the same time has good functionality, including smoothness and good durability.
[0029] In summary, the present invention has the following beneficial effects: 1) This invention provides an aqueous polyurethane / acrylate hybrid resin dispersion. By using ammonium sulfonate chain extender, the solid content of the dispersion is effectively increased while ensuring the stability and low viscosity of the dispersion. The solid content is higher than that of the commercially available aqueous polyurethane / acrylate dispersion used in the comparative example of this application, reaching not less than 52.5%, and even reaching 62.5% solid content. 2) This invention provides a waterborne polyurethane resin composition that can be applied to waterborne coatings for automobiles. The waterborne coatings for automobiles prepared by this invention have fast-drying properties. While ensuring the stability of other properties, the surface drying time and actual drying time are significantly shortened, which is beneficial to improving construction efficiency and greatly improving the production efficiency of the product. Attached Figure Description
[0030] Figure 1 This is a schematic diagram of the cross-cut test results of the present invention; Figure 2 This is a schematic diagram of the impact resistance test results of the present invention; Figure 3 This is a schematic diagram of the salt spray resistance test results of the present invention. Detailed Implementation
[0031] The present invention will be further explained and illustrated below with reference to specific embodiments.
[0032] This specific embodiment is merely an explanation of the present invention and is not intended to limit it. Any changes made by those skilled in the art after reading this specification, as long as they fall within the scope of the claims, will be protected by patent law.
[0033] As analyzed in the background section, automotive coatings not only need to provide aesthetic effects such as a smooth appearance and vibrant colors, but also need to possess various resistances, including resistance to acids, alkalis, salt spray, damp heat, and weathering. Simultaneously, they need to meet the ever-increasing demands for application performance, achieving rapid drying and improving production efficiency. To address this issue, this application provides a waterborne polyurethane / acrylate hybrid resin, a waterborne polyurethane resin composition, a waterborne automotive coating, and a method for preparing the same.
[0034] In the water-based automotive coatings of the following embodiments of this application, the following components are used: Component A: Aqueous resin dispersion A1 Self-contained waterborne polyurethane / acrylate hybrid resin dispersion Covestro Bayhydrol® A 145, A2 Waterborne Polyurethane / Acrylic Dispersion, 45% Solids Content A3 Waterborne Polyurethane / Acrylic Ester Dispersion, Huashi New Materials ACR-S6187, Solid Content 45% Component B: Defoamer B1 BYK Chemicals BYK-024 Component C: Film-forming aids C1 Jiangsu Sanmu Chemical Ethylene Glycol Monomethyl Ether Component D: Inorganic filler D1 Shanghai Yantai Waterborne Silver Aluminum Paste TW8210 Component E: Dispersant E1 BYK-191 Component F: Water-based pigment F1 Hangzhou Haivit Water-Based Black Surface Heat Spray HP2005-6 Component G: Carbodiimide curing agent G1 Daike Bio 2802 Component H: Other additives; H1 Wetting agent BYK-800 (BYK Chemicals) H2 leveling agent Evonik TEGO-410 H3 Rheology Modifier Xiamen Aikema Borchi Gel-0620 Self-prepared aqueous polyurethane / acrylate hybrid resin dispersion A1 is prepared as follows: Step S1: In a reactor equipped with a stirrer, temperature control device, and condenser, add polyol and remove water using a vacuum pump at 110–130°C until no more bubbles are visible in the polyol; cool to 78–82°C, add isocyanate, react for 15 min, add catalyst, and continue reacting for 3 h; cool to 58–62°C, then add chain extender and acetone, and continue reacting for 4 h; cool to 38–42°C, increase stirring speed, calculate the required amount of deionized water based on the set solid content of the polyurethane / acrylate hybrid resin dispersion (the solid content ranges from 52.5% to 65%), and add the required amount of deionized water within 5 min; then immediately add a neutralizing agent to neutralize, bringing the pH to 7.5–9.0; add an appropriate amount of chain extender ethylenediamine, extend the chain for 15 min, then remove acetone, and maintain the temperature for 4 h to obtain the polyurethane dispersion prepolymer.
[0035] In this step, acetone acts as a diluent. The amount of acetone added is determined according to (amount of isocyanate + amount of polyol) × (20%~35%). It is mainly used to prevent the viscosity of the system from being too high during emulsification and thus failing to emulsify.
[0036] In this step, the required amount of deionized water is calculated based on the set solid content of the polyurethane / acrylate hybrid resin dispersion. The specific calculation method is as follows: 1) When an organic solvent, such as acetone or butanone, is used as the initiator solvent, the required amount of deionized water is calculated according to the following formula, since the organic solvent completely evaporates during the reaction: Required amount of deionized water = (amount of polyol + amount of isocyanate + amount of chain extender + amount of neutralizer + amount of post-chain extender + amount of all acrylate monomers and / or methacrylate monomers and / or styrene monomers used in preparation step S2 + amount of pH adjuster) / set solid content - (amount of polyol + amount of isocyanate + amount of chain extender + amount of neutralizer + amount of post-chain extender + amount of all acrylate monomers and / or methacrylate monomers and / or styrene monomers used in preparation step S2 + amount of pH adjuster).
[0037] For example, when the solid content is set at 60%, and the total amount of the above raw materials added is 60 g, including polyol, isocyanate, chain extender, neutralizer, post-chain extender, all acrylate monomers and / or methacrylate monomers and / or styrene monomers used in preparation step S2, and pH adjuster, then the required amount of deionized water to be added is: 60 / (60%)-60=40 g.
[0038] 2) When deionized water is used as the solvent for the initiator, the required amount of deionized water is calculated according to the following formula: Required amount of deionized water = (amount of polyol + amount of isocyanate + amount of chain extender + amount of neutralizer + amount of post-chain extender + amount of all acrylate monomers and / or methacrylate monomers and / or styrene monomers used in preparation step S2 + amount of pH adjuster) / set solid content - (amount of polyol + amount of isocyanate + amount of chain extender + amount of neutralizer + amount of post-chain extender + amount of all acrylate monomers and / or methacrylate monomers and / or styrene monomers used in preparation step S2 + amount of pH adjuster) - amount of deionized water used to dissolve the initiator.
[0039] For example, if the solid content is set to 60%, the total amount of the above raw materials added is 60 g, including polyol, isocyanate, chain extender, neutralizer, post-chain extender, all acrylate monomers and / or methacrylate monomers and / or styrene monomers used in preparation step S2, and pH adjuster, and 5 g of deionized water is used as the dissolving initiator, then the required amount of deionized water to be added is: 60 / (60%)-60-5=35 g.
[0040] Step S2: Weigh acrylate monomers and / or methacrylate monomers and / or styrene monomers and mix them evenly to obtain a monomer mixture for later use. Weigh the initiator and dissolve it in a solvent (here, the solvent is an organic solvent or deionized water) to obtain an initiator solution for later use. Purge nitrogen gas into the polyurethane dispersion prepolymer obtained in Step S1 above, and heat it to 80-85°C under a nitrogen atmosphere. After stabilizing for 5 minutes, add the prepared monomer mixture and initiator solution dropwise simultaneously, with the monomer mixture added within 180 minutes and the initiator solution added within 200 minutes. Continue stirring and reacting for 1 hour, and add a pH adjuster to reach a pH of 7.5-9.0. If the initiator solution is dissolved in an organic solvent (here, the organic solvent is acetone or butanone), the solvent needs to be removed, and then the temperature is maintained for 8 hours. If the initiator solution is dissolved in deionized water as a solvent, directly maintain the temperature for 8 hours. Thus, an aqueous polyurethane / acrylate hybrid resin dispersion is obtained for later use. When dissolving the initiator, if an organic solvent is used, a 5% to 40% solution is generally prepared; if deionized water is used as the solvent, a 2.5% to 30% solution is generally prepared.
[0041] Specifically, depending on the raw materials (as shown in Table 1), aqueous polyurethane / polyacrylate hybrid resin dispersions are prepared using the above steps S1 and S2, including A11, A12, A13, A14, A15, A16, A17, A18, A19, A1A, A1B, A1C, as well as S1, S2, S3, S4, and S5.
[0042] Table 1. Raw material composition of waterborne polyurethane / polyacrylate hybrid resin dispersion (unit: g)
[0043]
[0044] The raw materials used include the following: a1 polyols: a11: Polyether polyol, PTMG2000, Mn=2000Da, Hyosung a12: Polyester polyol, PCL220N, Mn=2000Da, Daicel a13: Polycarbon / polyether hybrid polyol, PCE-220S, Mn=2000Da, Hefei Puli a2 isocyanate: a21: IPDI, Wanhua a22: HMDI, Evonik a3 Chain extender: a31: Winlink TM D60, Weiliang Optics
[0045] a32: DMPA (dimethylolpropionic acid), Joan resin a4 Neutralizing agents: Triethylamine (TEA), Maclean's Post-chain extender; ethylenediamine, Maclean's a5 acrylate monomers: a51: Hydroxyethyl acrylate (HEA), Shandong Yongbang a52: n-Butyl acrylate (BA), Shandong Yongbang A53: Isoborneol acrylate, Shanghai Guangyi a54: Acrylic acid (AA), Shandong Yongbang a6 methacrylate monomers a61: Hydroxyethyl methacrylate (HEMA), Shandong Yongbang a62: Isooctyl methacrylate (EHMA), Shandong Yongbang A63: Isoborneol methacrylate, Shanghai Guangyi a64: Methyl methacrylate (MMA), Shandong Yongbang A65: Methacrylic acid (MAA), Shandong Yongbang a66: Butyl methacrylate (BMA), Shandong Yongbang a67: 1-(2-hydroxyethyl)-2,2,6,6-tetramethylpiperidine methacrylate, self-synthesized a68: 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, Maclean a7 Styrene (St) A8 initiator: Ammonium persulfate (NSS), Maclean's a9 pH adjuster: A91: 25wt% ammonia solution, McLean a92: Glacial acetic acid, McLean The monomer A67 is also synthesized by itself. The synthesis path of A67 is as follows: In a three-necked flask equipped with a CaCl2 drying tube, 4-hydroxy-1-(2-hydroxyethyl)-2,2,6,6-tetramethylpiperidine and methacrylic acid were added in a molar ratio of 0.95:1. Anhydrous DMF was then added as a solvent to prepare a solution with a solid content of 64-65 wt%. The mixture was stirred under a nitrogen atmosphere until the reaction substrate was homogeneous. Then, 1% (by weight) of phosphotungstic acid was added as a catalyst, and the mixture was heated to 75°C and reacted for 6 hours. After the reaction was completed, the reaction mixture was diluted with twice the weight of DMF with water. The reactants were extracted three times with CH2Cl2. The organic phase was collected, washed three times with saturated brine, dried with anhydrous sodium sulfate, and 0.3 wt% of 4-methoxyphenol was added as a polymerization inhibitor. The mixture was concentrated, column-sected, and the solvent was removed to obtain product a67 (1-(2-hydroxyethyl)-2,2,6,6-tetramethylpiperidine methacrylate), with a yield of 42.5% and containing 2-6% acrylic acid monomer. No further purification was required, and the product was ready for use.
[0046] The specific data for each prepared waterborne polyurethane / acrylate hybrid resin dispersion are shown below, among which, HH represents the proportion of the total weight of hydroxyethyl acrylate and hydroxyethyl methacrylate to the total weight of all monomers, i.e.:
[0047] AA represents the percentage of the total weight of acrylic acid and methacrylic acid relative to the total weight of all monomers, i.e.:
[0048] UU represents the proportion of the total mass of structures (3), (4), (5), and (6) to the total mass of the prepared polyurethane / acrylate hybrid resin.
[0049] In this ratio calculation, the total mass of the polyurethane / acrylate hybrid resin refers to the mass of the polyurethane / acrylate hybrid resin itself after removing deionized water. Specifically, it is the sum of the amounts of polyol, isocyanate, chain extender, neutralizer, post-chain extender, all acrylate monomers and / or methacrylate monomers and / or styrene monomers used in preparation step S2, and pH adjuster.
[0050] PP represents the ratio of the total mass of the polyurethane component to the total mass of the polyacrylic acid component in the prepared polyurethane / acrylate hybrid resin, i.e.:
[0051] Determining the maximum solids content of the dispersion: Based on the formulation, design the formulation starting from 50% solids content with an interval of 2.5%, i.e., design solids content as 50%, 52.5%, 55%, 57.5%, 60%, 62.5%, and 65%. If the formulation cannot obtain a stable dispersion under a designed solids content condition, the maximum solids content of the dispersion obtained by the formulation shall be based on the actual measured solids content of the dispersion obtained under the previous set solids content condition. For example, if formulation A11 cannot obtain a stable dispersion at a designed solids content of 57.5%, the maximum solids content of the dispersion of formulation A11 is 54.8% as the actual measured solids content when the designed solids content is 55%.
[0052] Preparation method of waterborne polyurethane composition: Add B and C to A, i.e., the prepared polyurethane / acrylate hybrid resin dispersion (Examples 1-18 and Comparative Examples 1-16) or the commercially available aqueous resin solution (Comparative Examples 17 & 18), respectively, to form combination solution 1; under stirring at 200 r / min, add E, F, G and H sequentially to D to form combination solution 2; under continuous stirring, slowly transfer combination solution 1 to combination solution 2; continue stirring for 30 min to obtain the aqueous polyurethane composition. The specific parameters of the obtained polyurethane composition are shown in Table 2.
[0053] Table 2. Specific parameters of polyurethane compositions (unit: g)
[0054] Sample preparation: Take a new tinplate to be sprayed, first wipe the surface oil clean with anhydrous ethanol or acetone, then wipe it dry with degreased gauze and let it air dry for later use.
[0055] After adjusting the paint to the required viscosity, spray or brush it onto the surface-treated tinplate. Control the wet film thickness to 80±5μm at (23±2)℃ and 50% relative humidity, allowing it to surface dry naturally. Every 0.5 min, test the surface drying time according to GB / T 1728-2020 Method B and record the surface drying time T1. Continue at (23±2)℃ and 50% relative humidity, testing the actual drying time every 15 min according to GB / T1728-2020 Method A and record the actual drying time T2. Then, place the sample in an oven and bake it at 145℃ for 2 hours. Remove it and cure it for 7 days before testing.
[0056] Film thickness test: The film thickness was measured using a film thickness tester according to the measurement method in Clause 7.3 of GB / T 13452.2–2008 "Determination of film thickness of paints and varnishes".
[0057] Performance testing: Cross-cut test: Following the test method in GB / T 9286–2021 "Cross-cut test for paints and varnishes", the samples were subjected to a cross-cut test. The test results were graded from 0 to 5 according to the standard. Three samples were prepared for each formulation, and each sample was tested three times, for a total of nine test results. The average of the nine results was taken (rounded up to the nearest integer). Figure 1 As shown, 1) is the result of Example 1 (showing the overall test effect); 2) is the result of Example 9 (showing a partial enlarged view); 3) is the result of Comparative Example 14 (showing the overall test effect); 4) is the result of Comparative Example 8 (showing a partial enlarged view).
[0058] Impact resistance test: Following the test apparatus and conditions specified in GB / T 1732–2020 "Determination of Impact Resistance of Coatings", an iron ball was dropped freely from a height of 50 cm. The condition of the coating film on both sides of the impact point was observed using a 4x magnifying glass. Three samples were prepared for each formulation, and the test results were recorded at three different locations on each sample, for a total of nine test results. To facilitate statistical comparison of the nine repeated test results, this application uses a 0-5 classification based on the number of test points showing cracks, wrinkles, and / or peeling. This classification is only a statistical evaluation method for the repeated test results in this application and does not belong to the result levels specified in GB / T 1732-2020. No cracks, wrinkles, or peeling were detected in any test result, recorded as 0; one crack, wrinkle, or peeling was detected in one test result, recorded as 1; 2-3 cracks, wrinkles, or peeling were detected in 2; 3-5 cracks, wrinkles, or peeling were detected in 3; 5-7 cracks, wrinkles, or peeling were detected in 4; 8-9 cracks, wrinkles, or peeling were detected in 5; Figure 2 As shown, 1) is the result of Example 13 (partial magnified view); 2) is the result of Comparative Example 15 (partial magnified view); 3) is the result of Comparative Example 18 (partial magnified view); 4) is the result of Comparative Example 16 (overall test effect diagram). Water resistance test: The samples were tested according to GB / T 5209–1985 "Determination of water resistance of paints and varnishes - Immersion method". Three samples were prepared for each formulation and the test results were recorded for 360 hours. A sample with no blistering, wrinkling, peeling, obvious discoloration, or obvious loss of gloss was marked as 0; a sample with one noticeable abnormality and the other two samples without abnormality, or two or more samples with slight abnormalities, was marked as 1; a sample with one obvious abnormality and the other two samples with slight or no abnormalities, or two or more samples with noticeable abnormalities, was marked as 2; a sample with two or more obvious abnormalities was marked as 3. Weather resistance test: The samples were tested according to GB / T 1865–2009 "Artificial weathering and artificial radiation exposure (filtered xenon arc radiation) for paints and varnishes". Three samples were prepared for each formulation and irradiated for 2000 hours using a 12-minute wetting / 49-minute drying cycle. A sample with no abnormalities such as blistering, wrinkling, peeling, obvious discoloration, or obvious loss of gloss was marked as 0; a sample with one noticeable abnormality and the other two without abnormalities, or two or more with slight abnormalities, was marked as 1; a sample with one obvious abnormality and the other two with slight or no abnormalities, or two or more with noticeable abnormalities, was marked as 2; a sample with two or more obvious abnormalities was marked as 3. Acid resistance test: Samples were tested at (23±2)℃ in a 0.05 mol / L H2SO4 aqueous solution environment. Three samples were prepared for each formulation, and the test duration was 24 hours. The test results were recorded. A sample without any abnormalities such as bubbling, wrinkling, peeling, obvious discoloration, or obvious loss of gloss was marked as 0. A sample with one noticeable abnormality and the other two samples without abnormalities, or two or more samples with slight abnormalities, was marked as 1. A sample with one obvious abnormality and the other two samples with slight abnormalities or no abnormalities, or two or more samples with noticeable abnormalities, was marked as 2. A sample with two or more obvious abnormalities was marked as 3. Alkali resistance test: Samples were tested at (23±2)℃ in a 0.1 mol / L NaOH aqueous solution environment. Three samples were prepared for each formulation, and the test duration was 24 hours. The test results were recorded. A sample with no blistering, wrinkling, peeling, obvious discoloration, or obvious loss of gloss was marked as 0. A sample with one noticeable abnormality and the other two samples without abnormalities, or two or more samples with slight abnormalities, was marked as 1. A sample with one obvious abnormality and the other two samples with slight or no abnormalities, or two or more samples with noticeable abnormalities, was marked as 2. A sample with two or more obvious abnormalities was marked as 3. Moist heat resistance test: The samples were tested according to GB / T 1740-2007 "Determination of Moist Heat Resistance of Coating Film". Three samples were prepared for each formulation, and the test duration was 1000 hours. The test results were recorded. A sample with no abnormalities such as blistering, wrinkling, peeling, obvious discoloration, or obvious loss of gloss was marked as 0; a sample with one noticeable abnormality and the other two samples without abnormalities, or two or more samples with slight abnormalities, was marked as 1; a sample with one obvious abnormality and the other two samples with slight or no abnormalities, or two or more samples with noticeable abnormalities, was marked as 2; a sample with two or more obvious abnormalities was marked as 3. Salt spray resistance test: Samples were tested according to GB / T 1771–2007 "Determination of resistance to neutral salt spray in paints and varnishes". Three samples were prepared for each formulation. Before testing, an "X" was marked in the middle of the sample plate. The test lasted 2000 hours, and the results were recorded. A score of 0 was recorded if none of the three samples showed blistering, wrinkling, peeling, obvious discoloration, or obvious loss of gloss. A score of 1 was recorded if one of the three samples showed a noticeable abnormality while the other two did not, or if two or more samples showed slight abnormalities. A score of 2 was recorded if one of the three samples showed a significant abnormality while the other two showed slight abnormalities or no abnormalities, or if two or more samples showed noticeable abnormalities. A score of 3 was recorded if two or more of the three samples showed significant abnormalities. Figure 3 As shown, 1) is the result of Example 4 (one sample); 2) is the result of Comparative Example 2 (one sample); 3) is the result of Comparative Example 6 (one sample); and 4) is the result of Comparative Example 17 (one sample).
[0059] Test results:
[0060] From the above description, it can be seen that the present invention achieves the following effects: This application obtains a polyurethane / acrylate hybrid resin dispersion with a solid content of over 52.5% by using ammonium sulfonate chain extenders. When the obtained high-solids-content, low-viscosity resin mixture is applied to waterborne automotive coatings, it can be seen during application that, compared to comparative examples 17 and 18, the surface drying and hard drying times of the products are effectively improved, significantly reducing production time and increasing production efficiency. Simultaneously, the introduction of UV-absorbing and light-stabilizing groups enhances the weather resistance of the samples.
[0061] Comparative Examples 6-15 were used to investigate the effects of variations in the dosage of components A, C, D, E, and G on coating film performance, establishing the basis for defining the boundary conditions of components A, C, D, E, and G, and providing experimental evidence for determining the corresponding formulation ranges. When some components approach or exceed their respective ranges, one or more performance indicators show varying degrees of change. In other words, once this boundary is reached, the formulation's performance will be insufficient to some extent. For example, in Comparative Example 12, although the differences in the dosage of each raw material compared to Example 4 are small, the main difference lies in the dosage of additives. While the absolute amount of additives added to coating formulations is usually low, changes in their dosage can still significantly affect the dispersion state, film uniformity, and subsequent curing process of the system.
[0062] Specifically, the amount of dispersant E1 in Comparative Example 12 was reduced compared to Example 4. Although the reduction was small in terms of the amount added, it was approximately 33% lower in terms of relative change. The reduced amount of dispersant may weaken the dispersion and stabilization effect on pigments, fillers, or other components, thus affecting the uniformity of the coating system. This demonstrates that even if the absolute amount of some additives in the formulation changes slightly, their relative amount changes can still affect the final coating performance. Therefore, although Comparative Example 12 differs from Example 1 only in the amount of some raw materials, its performance test results may still be lower than those of Example 1.
[0063] Furthermore, the performance tests in this application typically employ multiple parallel samples or multiple test locations for evaluation, such as using 3 samples or a cumulative total of 9 test results for statistical analysis. During statistical evaluation, the sample whose entire set of test results meets the requirements is recorded as the optimal result; when one or more test results show abnormalities or defects, they are classified into the next lower level according to the number of defects. Therefore, as the formulation composition or dosage gradually deviates from the optimal range, the test results may initially show defects at a few test points, followed by more abnormalities at test points as the degree of deviation increases. This change is a gradual process, rather than necessarily manifesting as a sudden change in performance. Therefore, using the above statistical method to evaluate the performance differences between different formulations is reasonable. Thus, the results of comparative examples 6-15 are also reasonable.
Claims
1. A waterborne polyurethane / acrylate hybrid resin, characterized in that, It has the following structure (1): ; Among them, R1, R2, and R3 are independently C1~C12 alkyl groups, or cycloalkyl or phenyl groups with a maximum of two C1~C4 substituents; A and Q are independently O or NR, where R is H or C1~C4 alkyl; R0 is a C2~C7 trivalent alkyl group, and A and Q are not on the same carbon atom; pol The main chain is a polyurethane / acrylate hybrid resin; and by weight, the total mass of the ammonium sulfonate structure accounts for 2.55~3.75% of the total mass of the polyurethane / acrylate hybrid resin; the ratio of the total mass of the polyurethane component to the total mass of the polyacrylate component is (0.9~1.5):
1.
2. The method for preparing the waterborne polyurethane / acrylate hybrid resin as described in claim 1, characterized in that, It should include at least the following steps: Step S1: Add polyol to the reactor and remove water using a vacuum pump at 110-130℃ until no more bubbles appear in the polyol; cool to 78-82℃, add isocyanate, react for 15 min, add catalyst, and continue reacting for 3 h; cool to 58-62℃, then add chain extender and acetone, and continue reacting for 4 h; cool to 38-42℃, stir continuously, add deionized water within 5 min, then immediately add neutralizer to neutralize, reaching pH 7.5-9.0; add ethylenediamine as a chain extender and extend the chain for 15 min, then remove acetone and keep warm for 4 h to obtain polyurethane dispersion prepolymer; Step S2: Weigh acrylic acid and / or acrylate monomers and / or methacrylic acid and / or methacrylate monomers and / or styrene monomers and mix them evenly to obtain a monomer mixture for later use; weigh the initiator and dissolve it in a solvent to obtain an initiator solution for later use; introduce nitrogen gas into the polyurethane dispersion prepolymer obtained in Step S1 above, and heat it to 80~85℃ under a nitrogen atmosphere; after stabilizing for 5 min, add the pre-prepared monomer mixture and initiator solution dropwise, with the monomer mixture added within 180 min and the initiator solution added within 200 min; continue stirring and reacting for 1 h, add a pH adjuster, and the pH reaches 7.5~9.0 to obtain an aqueous polyurethane / acrylate hybrid resin dispersion.
3. The preparation method according to claim 2, characterized in that, The chain extender used contains the following structure (2): ; Among them, R1, R2, and R3 are independently C1~C12 alkyl groups, or cycloalkyl groups or phenyl groups with C1~C4 atoms; A and Q are independently O or NR, where R is H or C1~C4 alkyl group; R0 is a C2~C7 trivalent alkyl group, and A and Q are not on the same carbon atom.
4. The preparation method according to claim 2, characterized in that, The polyols used include one or more of polyester diols, polycarbonate diols, polyether diols, or hybrid diols, and the molecular weight of the polyols is between 1000 and 4000 Da, preferably between 1500 and 3000 Da. The isocyanates used include one or more of isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), dicyclohexylmethane diisocyanate (HMDI), diphenylmethane diisocyanate (MDI), hydrogenated diphenylmethylene diisocyanate (H6XDI), diphenylmethylene diisocyanate (XDI), lysine diisocyanate (LDI) and their oligomeric polyisocyanates, preferably one or more of IPDI, HDI, HMDI, H6XDI and their oligomeric polyisocyanates; The catalysts used include tertiary amine catalysts, morpholine catalysts, pyridine catalysts, piperazine catalysts, imidazole catalysts, and organometallic catalysts, with tertiary amine catalysts and organometallic catalysts being preferred, organometallic catalysts being more preferred, and organobismuth catalysts being even more preferred. The neutralizing agents used include ammonia, triethylamine (TEA) and / or dimethylethanolamine (DMEA), with TEA and / or DMEA being preferred.
5. The preparation method according to claim 2, characterized in that, The acrylate monomers used shall include at least one or more of the acrylate monomers modified with structures (3), (4), (5), and (6); the methacrylate monomers used shall include at least one of the methacrylate monomers modified with structures (3), (4), (5), and (6), and by weight, the total mass of monomers modified with structures (3), (4), (5), and (6) shall account for not less than 2.5% of the total mass of the monomer mixture; ; Among them, R4, R6, R7, R8 and R10 are independently H, C1-C12 alkyl, C1-C12 hydroxy-substituted alkyl, C1-C8 carbonyl; and R4, R6 and R7 contain only one acrylate group or methacrylate group; R8 and R10 contain only one acrylate group or methacrylate group. R5 and R9 are independently C1-C6 alkylene groups or none; R11 is a C1-C6 alkylene or C1-C6 alkene and is linked to an acrylate monomer; R12, R13, R14, R15, R16, R17, R18, R19, and R20 are independently H, C1-C12 alkyl, C1-C12 hydroxy-substituted alkyl, or C1-C12 alkoxy; and one of R12, R13, R14, R15, R16, R17, R18, R19, and R20 contains an acrylate group or a methacrylate group; and at least one of R16 and R20 is a phenolic hydroxyl group.
6. The preparation method according to claim 2, characterized in that, The acrylate monomers used include one or more of the following: methyl acrylate, ethyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, isooctyl acrylate, n-octyl acrylate, lauryl acrylate, hydroxyethyl acrylate, isobornyl acrylate, hydroxypropyl acrylate, and glycidyl acrylate; the methacrylate monomers used include one or more of the following: methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, isooctyl methacrylate, n-octyl methacrylate, lauryl methacrylate, hydroxyethyl methacrylate, isobornyl methacrylate, hydroxypropyl methacrylate, and glycidyl methacrylate. At the same time, at least one of hydroxyethyl acrylate (HEA) and hydroxyethyl methacrylate (HEMA) is contained, and the total weight of hydroxyethyl acrylate and hydroxyethyl methacrylate accounts for 15% to 35% of the total mass of the monomer mixture by weight. At the same time, it contains at least one of acrylic acid (AA) and methacrylic acid (MAA), and by weight, the total weight of acrylic acid and methacrylic acid accounts for 2.5% to 7.5% of the total mass of the monomer mixture; The initiators used include one or more of organic peroxide initiators, inorganic initiators, and azo initiators; inorganic initiators are preferred; inorganic persulfate initiators are more preferred.
7. A fast-drying water-based automotive coating, characterized in that, The waterborne polyurethane / acrylate hybrid resin of claim 1 comprises the following components in parts by weight: Component A: 28-40 parts by weight of waterborne polyurethane / acrylate hybrid resin dispersion; Component B: 0.2~1.0 parts by weight of defoamer; Component C: 0.5~7.5 parts by weight of film-forming aid; Component D: 12-22 parts by weight of inorganic filler; Component E: 0.6~1.2 parts by weight of dispersant; Component F: 7.5~17.5 parts by weight of water-based pigment; Component G: 0.5~5 parts by weight of curing agent; Component H: 0.3-5 parts by weight of other additives; The solid component of the aqueous polyurethane / acrylate hybrid resin dispersion is the polyurethane / acrylate hybrid resin as described in claim 1, the solvent is deionized water, the solid content of the aqueous polyurethane / acrylate hybrid resin dispersion is not less than 52.5 wt%, the viscosity at 25°C is not higher than 25 s when measured by a Tu-4 cup viscometer or not higher than 600 mPaS when measured by a rotational viscometer, and the conductivity of the deionized water used is not higher than 10 μS / cm.
8. The fast-drying water-based automotive coating according to claim 7, characterized in that: The curing agent is a carbodiimide-based curing agent, specifically comprising the following structure (7): ; Furthermore, the molecular weight of the curing agent is between 1200 and 6000, preferably between 1500 and 3500, and the carbodiimide structure accounts for no less than 8.5% of the total molecular chain weight.
9. The fast-drying water-based automotive coating according to claim 7, characterized in that: The defoamer includes one or more of silicone defoamers, polyether defoamers, and polyether-modified polysiloxane defoamers, with polyether-modified polysiloxane defoamers being preferred; The film-forming aids include one or more of alcohol-based film-forming aids, alcohol ether-based film-forming aids, alcohol ester-based film-forming aids, and N-methylpyrrolidone; The inorganic filler includes one or more of the following: aqueous silver-aluminum paste, titanium dioxide, mica powder, barium sulfate, and silicon dioxide, with aqueous silver-aluminum paste being preferred. The water-based color pastes include ordinary water-based color pastes, water-based color pastes with matte effects, water-based color pastes with metallic pigments, and water-based color pastes with pearl effects; The other additives include one or more of wetting agents, leveling agents, rheology modifiers, and cosolvents.
Citation Information
Patent Citations
Quick-drying water-based paint
CN114702885A
High-hardness high-wear-resistance quick-drying water-based automobile finish paint and preparation method thereof
CN115651520A